Philosophy of Baruch Spinoza in the light of the “second” discovery of the unconsciousness - Szmaglińska, Katarzyna (Folia Philosophica, 2010)
The paper deals with the concept of „unconsciousness” in the history of post-Cartesian philosophy. Focusing on B. Spinoza’s concept, the author analyses the possibility of a certain understanding of Spinoza’s hypothesis of the unconsciousness and his idea of psychology as speculative version of Freudianism (the practical part of Spinoza’s philosophy may be conceived as a version of Freudian analysis).